A measurement of the Q2, W and t dependences of deeply virtual Compton scattering at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Bellagamba, L; Boscherini, D; et al. (2009)
Deeply virtual Compton scattering, γ*p→γp has been measured in e+p collisions at HERA with the ZEUS detector using an integrated luminosity of 61.1 pb-1. Cross sections are presented as a function of the photon virtuality, Q2, and photon-proton centre-of-mass energy, W, for a wide region of the phase space, Q2 > 1.5GeV2 and 40 < W < 170GeV. A subsample of events in which the scattered proton is measured in the leading proton spectrometer, corresponding to an integrated luminosity of 31.3 pb-1, is used for the first direct measurement of the differential cross section as a function of t, where t is the square of the four-momentum transfer at the proton vertex. © SISSA 2009.